Clinical characteristics and outcomes of patients with COVID-19 admitted to the intensive care unit during the first and second waves of the pandemic in Brazil: a single-center retrospective cohort study - Thiago Domingos Corrêa; Thais Dias Midega; Ricardo Luiz Cordioli; Carmen Silvia Valente Barbas; Roberto Rabello Filho; Bruno Caldin da Silva; Moacyr Silva Júnior; Ricardo Kenji Nawa; Fabrício Rodrigues Torres de Carvalho; Gustavo Faissol Janot de Matos; Neide Marcela Lucinio; Rodrigo Dias Rodrigues; et al. (Einstein (São Paulo), 2023)
ABSTRACT Objective To describe and compare the clinical characteristics and outcomes of patients admitted to intensive care units during the first and second waves of the COVID-19 pandemic. Methods In this retrospective single-center cohort study, data were retrieved from the Epimed Monitor System; all adult patients admitted to the intensive care unit between March 4, 2020, and October 1, 2021, were included in the study. We compared the clinical characteristics and outcomes of patients admitted to the intensive care unit of a quaternary private hospital in São Paulo, Brazil, during the first (May 1, 2020, to August 31, 2020) and second (March 1, 2021, to June 30, 2021) waves of the COVID-19 pandemic. Results In total, 1,427 patients with COVID-19 were admitted to the intensive care unit during the first (421 patients) and second (1,006 patients) waves. Compared with the first wave group [median (IQR)], the second wave group was younger [57 (46-70) versus 67 (52-80) years; p<0.001], had a lower SAPS 3 Score [45 (42-52) versus 49 (43-57); p<0.001], lower SOFA Score on intensive care unit admission [3 (1-6) versus 4 (2-6); p=0.018], lower Charlson Comorbidity Index [0 (0-1) versus 1 (0-2); p<0.001], and were less frequently frail (10.4% versus 18.1%; p<0.001). The second wave group used more noninvasive ventilation (81.3% versus 53.4%; p<0.001) and high-flow nasal cannula (63.2% versus 23.0%; p<0.001) during their intensive care unit stay. The intensive care unit (11.3% versus 10.5%; p=0.696) and in-hospital mortality (12.3% versus 12.1%; p=0.998) rates did not differ between both waves. Conclusion In the first and second waves, patients with severe COVID-19 exhibited similar mortality rates and need for invasive organ support, despite the second wave group being younger and less severely ill at the time of intensive care unit admission.